CO2 ENRICHMENT AND MYCORRHIZAL EFFECTS ON CUTTING GROWTH AND SOME PHYSIOLOGICAL TRAITS OF CUTTINGS DURING ROOTING - Joanna Nowak; Jacek S. Nowak (Acta Scientiarum Polonorum: Hortorum Cultus, 2013)
Propagation conditions of bedding plants can eliminate or reduce the possibility of AMF inoculation of the root system during greenhouse production. Due to the ability of AMF to increase plant growth the effects of AMF and CO2 enrichment on rooting and some physiological traits of geranium and osteospermum cuttings were investigated. AMF and CO2 enrichment increased leaf number and fresh and dry weights of osteospermum shoots. Mycorrhization also significantly increased the length and fresh and dry weights of osteospermum roots formed in CO2 enriched atmosphere but it did not affect root system developed in ambient atmosphere. AMF increased the length and fresh weight of geranium roots, irrespectively of CO2 concentration, and dry weight of roots in CO2 enriched atmosphere. Transpiration and stomatal conductance values were higher in inoculated osteospermum at higher CO2 concentration. Mycorrhization and CO2 enrichment increased photosynthetic activity of garden geranium leaves and this effect was connected with the increased ratio of variable to maximum chlorophyll fluorescence (Fv/Fm).